Assessment of functional outcome of distal femur intra-articular fractures treated with locking compression plate - Mahajan, Neetin Pralhad; Ravesh, Ved Ashish; G. S., Prasanna Kumar; Chandanwale, Ajay; Gadod, Lalkar (International Journal of Research in Orthopaedics, 2019)
Background: Intra-articular distal femoral fracture makes up to 6% of all femur fractures. Because they damage the cartilage surface of the bone, intra-articular fractures can be more difficult to treat. The locking compression plates have nowadays proven to be gold standard in treating both simple as well as complex intra-articular distal femur fractures. This study is to evaluate the complications, functional and anatomical outcome of distal femur fractures, treated by open reduction and internal fixation using distal femoral locking compression plate. Methods: This is a retrospective study of 30 patients with intra articular distal femur fractures operated with distal femur locking compression plate during the period of 2015 to 2018 in a tertiary care hospital with age range from 17 to 71 years and follow up till 2 years. Fractures were classified according to AO classification and functional outcome assessed by using Neer criteria. Results: 10 cases had excellent score (33%), 16 cases (52%) had satisfactory score, 3 cases (11%) had unsatisfactory score and only one case had poor score. 85.1% of patients were in between satisfactory to excellent results. Complications observed were excessive bleeding, difficulty in reduction, superficial infections, knee stiffness, malalignment and limb length discrepancy. Conclusions: The distal femur locking compression plate is a good implant to be used for distal femur intra-articular fractures. Early surgery, anatomical reduction and early mobilisation are the prerequisites for good functional outcome. Comminution and bone defect on the medial side needs pillar reconstruction by fibular bone graft.